A freezer-resistant food packaging bag and a method of making the same

CN122445089BActive Publication Date: 2026-10-20ZIGUI XINPAI PACKAGING TECH CO LTD +1
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202610936805.X
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Filing Date
2026-06-26
Publication Date
2026-10-20
Estimated Expiration
2046-06-26

AI Technical Summary

Technical Problem

[0008]本申请提供了一种耐冷冻的食品包装袋及其制备方法,解决了现有食品包装袋在冷冻条件下因材料韧性下降、局部应力集中及裂纹易于萌生与扩展而导致抗冲击破损能力不足、易发生破袋的问题,从而提高食品包装袋在冷链运输过程中的使用可靠性

Benefits of technology

本申请通过在改性填料表面引入由甲基丙烯酸长直链烷基酯与甲基丙烯酸支链烷基酯共聚形成的接枝链段,在保证填料与聚乙烯基体良好相容性的同时,使填料界面区域形成具有非规整结构特征的过渡层,从而有效降低填料对聚乙烯链段规整结晶的诱导作用,减少局部高结晶度、高刚性区域的形成。

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure SMS_1
    Figure SMS_1
Patent Text Reader

Abstract

The application provides a freezing-resistant food packaging bag and a preparation method thereof. The food packaging bag comprises the following raw materials in parts by mass: 100 parts of low-density polyethylene, 1-5 parts of modified filler and 0.1-1 parts of antioxidant. The surface of the modified filler is grafted with a copolymer chain segment of long straight-chain alkyl methacrylate and branched-chain alkyl methacrylate, wherein the number of carbon atoms of the long straight-chain alkyl is 12-18, and the number of carbon atoms of the branched-chain alkyl is 6-10. By introducing the chain segment formed by copolymerization of long straight-chain alkyl methacrylate and branched-chain alkyl methacrylate on the surface of the modified filler, the filler can not only play a role in dispersing stress and hindering crack propagation in the polyethylene matrix, but also reduce the induction of the filler interface to local regular crystallization of polyethylene, thereby reducing the tendency of forming a high-crystallinity and high-rigidity region around the filler, and improving the impact resistance and freezing resistance of the food packaging bag in a low-temperature environment.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] This application relates to the field of food packaging bag technology, specifically to a freeze-resistant food packaging bag and its preparation method. Background Technology

[0002] Food packaging bags are an important component of the cold chain transportation system, widely used in the storage and transportation of frozen meat products, aquatic products, and quick-frozen foods. Under cold chain conditions, food packaging bags not only need to have good sealing performance and mechanical strength, but also need to maintain stable structural performance in low-temperature environments to prevent breakage during handling, stacking, or dropping, which could lead to leakage or contamination of the contents.

[0003] Currently, most food packaging bags are made of polyethylene, such as low-density polyethylene or linear low-density polyethylene. These materials offer advantages such as good processability, low cost, and high flexibility. However, at low temperatures, the molecular chain mobility of polyethylene decreases significantly, resulting in increased rigidity and decreased toughness. Under freezing conditions, the film material is more prone to brittle fracture when subjected to impact, bending, or localized stress, leading to packaging bag damage.

[0004] In actual cold chain transportation, packaging bags typically undergo various mechanical actions such as handling, stacking, collisions, and drops. When packaging bags are frozen, their impact resistance decreases significantly, especially at the edges, creases, or near heat-sealed areas, where stress concentration points easily form, inducing cracks that propagate rapidly and ultimately leading to bag breakage. Therefore, improving the impact resistance and breakage resistance of food packaging bags under low-temperature conditions is a pressing technical problem that needs to be solved in this field.

[0005] To improve the low-temperature performance of polyethylene materials, existing technologies typically employ the addition of elastomers or rubber-based toughening agents to alleviate low-temperature brittleness by increasing the overall flexibility of the material. However, these methods often require high dosages, which can negatively impact the material's rigidity, processing stability, heat-sealing performance, and appearance. Furthermore, they increase material costs to some extent, making it difficult to balance low-temperature breakage resistance with the overall performance of the packaging material.

[0006] Some technologies have attempted to modify polyethylene materials by introducing inorganic fillers. By treating the surface of inorganic fillers with coupling agents or other interface modifications, the dispersibility and interfacial compatibility of the fillers in the polymer matrix can be improved to some extent. However, existing interfacial modifications mostly focus on improving the compatibility or bonding force between the filler and the polymer, essentially remaining at the level of conventional interfacial wetting or interfacial bonding improvement. At low temperatures, the fracture behavior of polyethylene materials is not only related to the filler dispersion and interfacial bonding state but also closely related to the local microstructure surrounding the filler. Even if the filler is relatively uniformly dispersed in the matrix, when its interfacial structure still exhibits strong regularity or rigidity, the filler and its interfacial region may still act as heterogeneous nucleation sites, promoting the formation of more regular or complete crystal structures locally, thus exhibiting higher rigidity and brittleness in low-temperature environments. Under impact or stress, these regions are more prone to stress concentration and become the starting points for crack initiation and propagation.

[0007] Therefore, how to reduce the risk of crack propagation induced by low-temperature impact at the filler interface or local rigid areas without significantly affecting the original processing performance and overall performance of polyethylene materials, and improve the impact resistance of food packaging bags during cold chain transportation, remains a technical problem that needs further research and solutions in this field. Summary of the Invention

[0008] This application provides a freeze-resistant food packaging bag and its preparation method, which solves the problem that existing food packaging bags are prone to damage due to insufficient impact resistance and easy breakage under freezing conditions, caused by decreased material toughness, local stress concentration, and easy initiation and propagation of cracks. This improves the reliability of food packaging bags in cold chain transportation.

[0009] In a first aspect, this application provides a freeze-resistant food packaging bag, comprising the following raw materials in parts by weight: 100 parts low-density polyethylene, 1 to 5 parts modified filler, and 0.1 to 1 part antioxidant; The modified filler has copolymer segments of long-chain alkyl methacrylate and branched-chain alkyl methacrylate grafted onto its surface, wherein the long-chain alkyl ester has 12 to 18 carbon atoms and the branched-chain alkyl ester has 6 to 10 carbon atoms.

[0010] According to this application, by introducing grafted segments formed by copolymerization of long-chain alkyl methacrylate and branched alkyl methacrylate on the surface of the modified filler, the filler can not only play the role of dispersing stress and hindering crack propagation in the polyethylene matrix, but also reduce the induction effect of the filler interface on the local regular crystallization of polyethylene, thereby reducing the tendency of forming highly crystalline and rigid regions around the filler and improving the impact resistance and freezing resistance of food packaging bags in low-temperature environments.

[0011] Specifically, low-density polyethylene (LDPE), as a continuous phase matrix, exhibits good film-forming properties and flexibility. However, its molecular chain segment mobility decreases in frozen environments, making the material more susceptible to brittle fracture. Adding fillers to the polyethylene matrix, with improved compatibility and bonding between the filler and matrix, can help disperse external impact stress and impede, deflect, or passivate crack propagation paths, thus improving the material's impact resistance. However, filler surfaces without proper interface control typically possess high surface energy or strong interfacial regularity, making them prone to acting as heterogeneous nucleation sites during polyethylene crystallization. This allows polyethylene chains around the filler to more readily align and crystallize, forming locally highly crystalline and rigid interfacial regions. These regions exhibit even lower chain segment mobility at low temperatures, making them susceptible to stress concentration under impact or drop, potentially becoming the initiation and propagation sites for cracks.

[0012] In this application, the copolymer segments grafted onto the surface of the modified filler contain both long-chain alkyl structures and branched-chain alkyl structures. The long-chain alkyl structures exhibit good hydrophobic compatibility with the polyethylene molecular chains, improving the interfacial bonding and dispersion between the filler and the low-density polyethylene matrix. This ensures stable filler distribution within the matrix and reduces defects caused by filler agglomeration or interfacial debonding. The branched-chain alkyl structures introduce a non-linear spatial configuration into the grafted layer, preventing the organic layer on the filler surface from exhibiting a single, regular long-chain arrangement. This weakens the inducing effect of the filler interface on the regular stacking and localized crystal growth of the polyethylene segments.

[0013] Therefore, the long-chain alkyl structure provides the interface matching and dispersion basis, while the branched alkyl structure provides the non-regular disturbance effect. Together, they create a relatively soft, low-regularity interface transition region around the filler. This interface transition region is beneficial for the filler to disperse impact stress and crack propagation, and it also reduces the risk of the filler acting as a heterogeneous nucleation site, leading to the formation of locally highly crystalline and rigid regions. Consequently, in freezing environments, the material is less prone to rapid crack propagation due to localized embrittlement at the filler interface, and food packaging bags exhibit better impact resistance in cold chain transportation scenarios such as drops and collisions.

[0014] In some embodiments, the modified filler is prepared by the following steps: S1: Aminated filler and carboxyl-containing trithiocarbonate RAFT chain transfer agent are dispersed in N,N-dimethylformamide to induce amidation reaction between the aminated filler and the carboxyl-containing trithiocarbonate RAFT chain transfer agent, thereby obtaining RAFT active filler. S2: The RAFT active filler, long-chain alkyl methacrylate and branched-chain alkyl methacrylate are dispersed in toluene, and the long-chain alkyl methacrylate and branched-chain alkyl methacrylate undergo RAFT controlled polymerization reaction on the surface of the RAFT active filler to obtain the modified filler.

[0015] In some of the above embodiments, a carboxyl-containing trithiocarbonate-based RAFT chain transfer agent is introduced onto the surface of the aminated filler. This chain transfer agent contains carboxyl groups and trithiocarbonate structures. The carboxyl groups can undergo amidation reactions with the amino groups on the surface of the aminated filler, and the trithiocarbonate structures are used to regulate the subsequent RAFT-controlled polymerization of methacrylate monomers. This creates active sites with chain transfer function on the filler surface, allowing the subsequent polymerization process to mainly occur near the filler interface. Compared to direct free radical grafting or physical coating, this method is beneficial for distributing grafted chains more uniformly and stably on the filler surface, thereby avoiding the generation of a large amount of free polymer and improving the stability of the interfacial layer structure.

[0016] Under RAFT regulation, long-chain alkyl methacrylates and branched-chain alkyl methacrylates can form relatively uniform copolymer segments on the filler surface, resulting in a synergistic spatial distribution of the long-chain and branched structures. On the one hand, the long-chain alkyl structure improves the interfacial compatibility between the grafted layer and the polyethylene matrix, leading to more uniform dispersion of the modified filler in the matrix. On the other hand, the branched-chain alkyl structure introduces irregular arrangement characteristics in the grafted layer, which helps to weaken the inducing effect of the filler interface on the regular crystallization of polyethylene segments, thereby reducing the possibility of forming highly crystalline regions at the filler interface.

[0017] In some embodiments, step S1 includes: Ten parts of aminated filler, 0.2-1 parts of carboxyl-containing trithiocarbonate RAFT chain transfer agent, 0.1-0.4 parts of N,N'-dicyclohexylcarbonimide and 0.05-0.2 parts of N-hydroxysuccinimide were dispersed in 70-120 parts of N,N-dimethylformamide and reacted at 30-50℃ for 8-12 h under a nitrogen atmosphere to obtain RAFT active filler.

[0018] In some of the above embodiments, the carboxyl groups in the RAFT chain transfer agent are activated by N,N'-dicyclohexylcarboimide and N-hydroxysuccinimide, enabling them to undergo an amidation reaction with the amino groups on the surface of the aminated filler, thereby stably introducing the RAFT active groups onto the filler surface. This method facilitates the formation of relatively uniformly distributed active sites on the filler surface, providing a basis for subsequent graft polymerization, and thus helps to improve the stability and control effect of the modified filler interface structure.

[0019] In some embodiments, in step S1, the aminated filler is obtained by treating silica with an aminosilane coupling agent, and the silica has an average particle size of 0.05~0.2μm; the carboxyl-containing trithiocarbonate RAFT chain transfer agent includes 2-methyl-2-[(dodecylthiocarbonyl)thio]propionic acid.

[0020] In some of the above embodiments, surface treatment of silica with an aminosilane coupling agent is beneficial for introducing amino functional groups on its surface, thereby providing reaction sites for subsequent amidation reactions; the selection of the above-mentioned carboxyl-containing trithiocarbonate RAFT chain transfer agent is beneficial for introducing stable RAFT active groups on the filler surface, thereby meeting the needs of subsequent graft polymerization.

[0021] In some embodiments, the aminated filler is prepared by the following method: Disperse 10 parts of silica and 1-2 parts of aminosilane coupling agent in 100-200 parts of ethanol aqueous solution, and react at 60-80℃ for 3-6 hours to obtain aminated filler.

[0022] In some of the above embodiments, surface treatment of silica with an aminosilane coupling agent is beneficial for introducing amino functional groups onto its surface, thereby providing a stable reaction basis for subsequent modification reactions.

[0023] In some implementations, step S2 includes: Ten parts of RAFT active filler, 4-8 parts of long-chain alkyl methacrylate, 0.5-1.5 parts of branched-chain alkyl methacrylate, and 0.03-0.1 parts of azobisisobutyronitrile were dispersed in 70-120 parts of toluene and reacted at 70-85°C for 5-8 hours under a nitrogen atmosphere to obtain the modified filler.

[0024] In some of the above embodiments, by controlling the ratio of long-chain alkyl methacrylate to branched-chain alkyl methacrylate, the relative content of long-chain and branched structures in the graft copolymer segments can be adjusted, thereby achieving appropriate structural disturbance while ensuring interfacial compatibility. Simultaneously, by controlling the total monomer dosage, initiator dosage, and reaction time, the grafted segments are kept within a suitable length range, thus avoiding the formation of excessively thick or sparse interfacial layers. This facilitates the construction of a graft layer on the filler surface that combines interfacial compatibility and irregularity, enabling the filler to be uniformly dispersed in the polyethylene matrix while reducing the tendency for induced regular crystallization in the interfacial region. This, in turn, more effectively inhibits crack initiation and propagation under low-temperature conditions, improving the material's freeze-thaw resistance.

[0025] In some embodiments, in step S2, the long-chain alkyl methacrylate includes lauryl methacrylate and octadecyl methacrylate, wherein the mass ratio of lauryl methacrylate to octadecyl methacrylate is (2~4):1.

[0026] In some of the above embodiments, the inventors discovered that when lauryl methacrylate and octadecyl methacrylate are compounded and used in the above ratio, the resulting grafted layer exhibits superior overall performance under low-temperature conditions. The possible reason for this is that the longer linear alkyl chain provided by octadecyl methacrylate helps enhance the hydrophobic compatibility between the grafted layer and the polyethylene matrix, giving the filler a certain interfacial anchoring ability within the matrix. Meanwhile, the relatively short chain length of lauryl methacrylate introduces chain length differences in the grafted layer, making it difficult for the chain segments to form a regular arrangement, thereby enhancing the irregularity and flexibility of the interfacial region. Simultaneously, the introduction of branched alkyl methacrylate further perturbs the linear alkyl chain segments spatially, causing the grafted layer to exhibit multi-scale irregular structural characteristics. This structure retains a certain chain segment adhesion ability in the interfacial region while avoiding an overly dense or ordered stacking state, thereby further weakening the inducing effect of the filler interface on the regular crystallization of polyethylene chain segments.

[0027] When these three factors work synergistically, while ensuring the stability of the interfacial bonding, the differences in chain length and the disturbance of the branches in the grafted layers work together to prevent the formation of locally high crystallinity and high rigidity structures in the filler interface region. Therefore, under low-temperature conditions, this interfacial structure is more conducive to dispersing stress and inhibiting the initiation and propagation of cracks along the interface, thus enabling the material to exhibit superior freeze-thaw resistance.

[0028] In some embodiments, the branched alkyl methacrylate includes 2-ethylhexyl methacrylate.

[0029] In some of the above embodiments, 2-ethylhexyl methacrylate is selected as a branched monomer, which is beneficial to introduce branched structures into the grafted layer, thereby disturbing the regular arrangement of the interface segments and further enhancing the irregularity of the interface layer.

[0030] In some embodiments, the low-density polyethylene has a melt flow rate of 1.5~2.5 g / 10 min at 190°C and 2.16 kg. Based on the above embodiments, selecting low-density polyethylene with a melt flow rate of 1.5~2.5 g / 10 min is beneficial in maintaining appropriate molecular chain length and mechanical properties while ensuring good processing fluidity of the material, thereby enabling the resulting packaging bag to have both film-forming stability and low-temperature performance.

[0031] In some embodiments, the antioxidant includes at least one of antioxidant 1010 and antioxidant 168. Based on the above embodiments, antioxidant 1010 and antioxidant 168 can be used alone or in combination, which is beneficial for inhibiting the thermo-oxidative degradation of polyethylene during material processing and use, thereby improving the stability of the material and avoiding the impact of performance degradation on the use of the packaging bag.

[0032] Secondly, this application provides a method for preparing a freeze-resistant food packaging bag, comprising: Provide the raw materials included in the food packaging bag according to any embodiment of the first aspect; The raw materials are melt-blended, granulated, and blown into film to obtain food packaging bags.

[0033] According to this application, by adopting the raw material system of the first aspect of food packaging bags and combining melt blending and blown film processes, the modified filler can be uniformly dispersed in the polyethylene matrix and form a stable interfacial structure, thereby ensuring processing performance while improving the impact resistance of food packaging bags under low temperature conditions.

[0034] Compared with the prior art, the beneficial effects of this application are at least as follows: This application introduces grafted segments formed by copolymerization of long-chain alkyl methacrylate and branched alkyl methacrylate on the surface of the modified filler. While ensuring good compatibility between the filler and the polyethylene matrix, it also creates a transition layer with irregular structural characteristics at the filler interface, thereby effectively reducing the inducing effect of the filler on the regular crystallization of polyethylene segments and reducing the formation of local high crystallinity and high rigidity regions.

[0035] Meanwhile, the grafted structure allows the filler to both disperse stress and inhibit crack propagation within the material, while also preventing stress concentration caused by increased interfacial rigidity. This makes it more effective at suppressing crack initiation and propagation at low temperatures. Consequently, food packaging bags are less prone to breakage when subjected to drops or impacts during cold chain transportation, exhibiting superior freeze resistance and impact damage resistance.

[0036] Furthermore, this application achieves performance improvement through structural design without the need to introduce a large amount of elastomer or rubber toughening components, thereby improving the overall performance of food packaging bags while maintaining material processing performance, heat sealing performance, and appearance performance. Detailed Implementation

[0037] The various embodiments or implementation schemes in this specification are described in a progressive manner, with each embodiment focusing on the differences from other embodiments.

[0038] In the description of this specification, the references to terms such as "one embodiment," "some embodiments," "illustrative embodiment," "example," "specific example," or "some examples," etc., indicate that a specific feature, structure, material, or characteristic described in connection with an embodiment or example is included in at least one embodiment or example of this application. In this specification, the illustrative expressions of the above terms do not necessarily refer to the same embodiment or example. Furthermore, the specific features, structures, materials, or characteristics described may be combined in any suitable manner in one or more embodiments or examples.

[0039] Furthermore, the terms "first" and "second" are used for descriptive purposes only and should not be construed as indicating or implying relative importance or implicitly specifying the number of technical features indicated. Thus, a feature defined as "first" or "second" may explicitly or implicitly include at least one of that feature. In the description of this application, "multiple" means at least two, such as two, three, etc., unless otherwise explicitly specified.

[0040] In this specification, unless otherwise specified, "parts" refers to "parts by weight".

[0041] The following describes embodiments of this application. The embodiments described below are exemplary and are only used to explain this application, and should not be construed as limiting this application. Where specific techniques or conditions are not specified in the embodiments, they are performed according to the techniques or conditions described in the literature in this field or according to the product instructions. Reagents or instruments used, unless otherwise specified, are all conventional products that can be obtained commercially.

[0042] Silica, with an average particle size of approximately 0.1 μm.

[0043] Low-density polyethylene, model 2426H, Zhongcheng, has a melt flow rate of approximately 2 g / 10 min at 190℃ and 2.16 kg.

[0044] 2-Methyl-2-[(dodecylthiocarbamate)thio]propionic acid, CAS number 461642-78-4, RAFT chain transfer agent.

[0045] Preparation of aminated filler: 10 parts of silica were weighed and added to 150 parts of an ethanol / water mixture (volume ratio 95:5). The mixture was ultrasonically dispersed for 20 min to ensure uniform dispersion of silica in the system. Subsequently, 1.5 parts of γ-aminopropyltriethoxysilane were added, and the mixture was stirred at 70 °C for 4 h. After the reaction was completed, the system was centrifuged, and the resulting solid was washed three times with ethanol to remove unreacted coupling agent and byproducts. The washed solid was then vacuum dried at 60 °C for 12 h to obtain the aminated filler.

[0046] Preparation Example 1 Preparation of modified fillers: S1: Weigh 10 parts of the above-mentioned aminated filler and add it to 100 parts of N,N-dimethylformamide, dispersing it evenly under stirring. Then, add 0.5 parts of 2-methyl-2-[(dodecylthiocarbamoyl)thio]propionic acid, 0.2 parts of N,N'-dicyclohexylcarbamoylimide, and 0.1 parts of N-hydroxysuccinimide in sequence. Purge the air in the system with nitrogen and stir the reaction at 40°C for 10 hours under nitrogen protection. After the reaction is complete, filter the system and separate the solid. Wash the obtained solid with N,N-dimethylformamide and ethanol in sequence to remove unreacted reagents and byproducts. Dry the washed solid under vacuum at 60°C to obtain the RAFT active filler.

[0047] S2: Weigh 10 parts of RAFT active filler and add it to 100 parts of toluene. Disperse evenly under stirring. Then add 4.8 parts of lauryl methacrylate, 1.6 parts of octadecyl methacrylate, and 1.2 parts of 2-ethylhexyl methacrylate. Continue stirring until evenly mixed. Then add 0.06 parts of azobisisobutyronitrile as an initiator. Purge the system with nitrogen and heat to 75°C under nitrogen protection. Maintain the reaction for 6 hours. After the reaction is complete, cool to room temperature and centrifuge the system. Wash the obtained solid several times with toluene and ethanol to remove unreacted monomers and free polymers. Dry the washed solid under vacuum at 60°C to obtain modified filler A.

[0048] Preparation Example 2 Preparation of modified fillers: The preparation method is largely the same as in Example 1, except that step S2 is different, specifically: S2: Weigh 10 parts of RAFT active filler and add it to 100 parts of toluene. Disperse evenly under stirring. Then add 6.4 parts of lauryl methacrylate and 1.2 parts of 2-ethylhexyl methacrylate, and continue stirring until evenly mixed. Add 0.06 parts of azobisisobutyronitrile as an initiator. Purge the system with nitrogen and heat to 75°C under nitrogen protection, maintaining the reaction for 6 hours. After the reaction is complete, cool to room temperature and centrifuge the system. Wash the obtained solid several times with toluene and ethanol to remove unreacted monomers and free polymers. Dry the washed solid under vacuum at 60°C to obtain modified filler B.

[0049] Preparation Example 3 Preparation of modified fillers: The preparation method is largely the same as in Example 1, except that step S2 is different, specifically: S2: Weigh 10 parts of RAFT active filler and add it to 100 parts of toluene. Disperse the mixture evenly under stirring. Then add 5.4 parts of lauryl methacrylate, 1 part of octadecyl methacrylate, and 1.2 parts of 2-ethylhexyl methacrylate. Continue stirring until the mixture is homogeneous. Add 0.06 parts of azobisisobutyronitrile as an initiator. Purge the system with nitrogen and heat to 75°C under nitrogen protection. Maintain the reaction for 6 hours. After the reaction is complete, cool to room temperature and centrifuge the system. Wash the obtained solid several times with toluene and ethanol to remove unreacted monomers and free polymers. Dry the washed solid under vacuum at 60°C to obtain modified filler C.

[0050] Preparation Example 4 Preparation of modified fillers: The preparation method is largely the same as in Example 1, except that step S2 is different, specifically: S2: Weigh 10 parts of RAFT active filler and add it to 100 parts of toluene. Disperse evenly under stirring. Then add 3.2 parts of lauryl methacrylate, 3.2 parts of octadecyl methacrylate, and 1.2 parts of 2-ethylhexyl methacrylate. Continue stirring until evenly mixed. Then add 0.06 parts of azobisisobutyronitrile as an initiator. Purge the system with nitrogen and heat to 75°C under nitrogen protection. Maintain the reaction for 6 hours. After the reaction is complete, cool to room temperature and centrifuge the system. Wash the obtained solid several times with toluene and ethanol to remove unreacted monomers and free polymers. Dry the washed solid under vacuum at 60°C to obtain modified filler D.

[0051] Preparation Example 5 Preparation of modified fillers: The preparation method is largely the same as in Example 1, except that step S2 is different, specifically: S2: Weigh 10 parts of RAFT active filler and add it to 100 parts of toluene. Disperse evenly under stirring. Then add 6.4 parts of octadecyl methacrylate and 1.2 parts of 2-ethylhexyl methacrylate, and continue stirring until evenly mixed. Add 0.06 parts of azobisisobutyronitrile as an initiator. Purge the system with nitrogen and heat to 75°C under nitrogen protection, maintaining the reaction for 6 hours. After the reaction is complete, cool to room temperature and centrifuge the system. Wash the obtained solid several times with toluene and ethanol to remove unreacted monomers and free polymers. Dry the washed solid under vacuum at 60°C to obtain modified filler E.

[0052] Comparative Preparation Example 1 Preparation of modified fillers: The preparation method is largely the same as in Example 1, except that step S2 is different, specifically: Ten parts of RAFT active filler were weighed and added to 100 parts of toluene. The mixture was dispersed evenly under stirring. Then, 5.7 parts of lauryl methacrylate and 1.9 parts of octadecyl methacrylate were added, and stirring continued until homogeneous. Finally, 0.06 parts of azobisisobutyronitrile (AIB) were added as an initiator. The system was purged with nitrogen, and the temperature was raised to 75°C under nitrogen protection, maintaining the reaction for 6 hours. After the reaction, the mixture was cooled to room temperature, and the system was centrifuged. The resulting solid was washed several times with toluene and ethanol to remove unreacted monomers and free polymers. The washed solid was then vacuum dried at 60°C to obtain modified filler F.

[0053] Comparative Preparation Example 2 Preparation of modified fillers: The preparation method is largely the same as in Example 1, except that step S2 is different, specifically: Ten parts of RAFT active filler were weighed and added to 100 parts of toluene. The mixture was dispersed evenly under stirring. Then, 7.6 parts of 2-ethylhexyl methacrylate were added, and stirring continued until homogeneous. Finally, 0.06 parts of azobisisobutyronitrile (AIBN) were added as an initiator. The system was purged with nitrogen, and the temperature was raised to 75°C under nitrogen protection, maintaining the reaction for 6 hours. After the reaction, the mixture was cooled to room temperature, and the system was centrifuged. The resulting solid was washed several times with toluene and ethanol to remove unreacted monomers and free polymers. The washed solid was then vacuum dried at 60°C to obtain modified filler G.

[0054] Example 1 Preparation of freeze-resistant food packaging bags: Weigh 100 parts of low-density polyethylene as the matrix resin, add 2 parts of modified filler A, 0.2 parts of antioxidant 1010 and 0.2 parts of antioxidant 168, and premix in a high-speed mixer at room temperature at 600 rpm for 10 min to ensure uniform dispersion of each component and obtain the premix.

[0055] The obtained premixed material was added to a twin-screw extruder for melt blending and extrusion. The temperatures of each zone of the extruder were set sequentially as follows: zone 1 150℃, zone 2 165℃, zone 3 175℃, zone 4 185℃, and die head 190℃. The screw speed was 250 rpm. After melt blending, the material was extruded into strips, cooled by water cooling, and then pelletized to obtain modified polyethylene masterbatch.

[0056] The obtained masterbatch was added to a blown film machine for blown film forming. The barrel temperature was set to 160℃, 170℃, 180℃ and 190℃ in sequence, the die head temperature was 190℃, the screw speed was 60 rpm, the blow-up ratio was 2.5 and the traction ratio was 4.0, and a freeze-resistant food packaging bag film with a thickness of about 50μm was obtained.

[0057] Example 2 Preparation of freeze-resistant food packaging bags: It is largely the same as Example 1, except that modified filler B is used instead of modified filler A.

[0058] Example 3 Preparation of freeze-resistant food packaging bags: It is largely the same as Example 1, except that modified filler C is used instead of modified filler A.

[0059] Example 4 Preparation of freeze-resistant food packaging bags: It is largely the same as Example 1, except that modified filler D is used instead of modified filler A.

[0060] Example 5 Preparation of freeze-resistant food packaging bags: It is largely the same as Example 1, except that modified filler E is used instead of modified filler A.

[0061] Comparative Example 1 Preparation of freeze-resistant food packaging bags: It is largely the same as Example 1, except that modified filler F is used instead of modified filler A.

[0062] Comparative Example 2 Preparation of freeze-resistant food packaging bags: It is largely the same as Example 1, except that modified filler G is used instead of modified filler A.

[0063] Test section Test on bag breakage rate after freezing: Take food packaging bag samples of the same size obtained from the above-described embodiments and comparative examples. Add 500 parts of hydrogel simulant to each packaging bag. The hydrogel simulant is formed by mixing 98.5 parts of water and 1.5 parts of sodium carboxymethyl cellulose with a weight average molecular weight of 100,000 and then allowing it to stand. It is used to simulate the contents of frozen food.

[0064] The packaging bags were heat-sealed using a heat-sealing machine at a temperature of 150℃, a pressure of 0.2MPa, a sealing time of 1.0s, and a sealing width of 10mm. After heat sealing, the integrity of the seal was checked, and samples with defective seals were discarded.

[0065] The heat-sealed samples were frozen at -18°C for 24 hours. After freezing, the samples were removed and a drop test was conducted within 1 minute of removal. During the test, the packaging bag was dropped freely from a height of 1.0m onto a flat, hard cement surface with the sealed edge facing down. Each sample was dropped once.

[0066] After the drop test, observe whether the packaging bag is ruptured, the seal is broken, or the contents leak. Record the number of ruptured bags. The total number of test samples is 50. Calculate the following formula: Freezing drop breakage rate (%) = Number of broken samples / Total number of test samples × 100%.

[0067] Impact performance test of darts after freezing: The dart impact test was conducted according to Method A of GB / T 9639.1-2008 "Test Methods for Impact Resistance of Plastic Films and Sheets - Free Falling Dart Method - Part 1: Step Method". Film samples were cut into specimens conforming to the standard requirements and frozen at -18℃ for 24 hours. After freezing, the specimens were removed, and the test was completed within 1 minute of removal.

[0068] The test was conducted using the dart drop and drop distance specified in Method A. The mass of the dart that caused a 50% probability of breakage of the sample was determined and recorded as the impact breakage mass after freezing, in grams.

[0069] The results are shown in Table 1.

[0070] Table 1 According to Table 1, compared with Comparative Examples 1 and 2, all embodiments showed lower drop breakage rates and higher impact breakage quality after freezing. This indicates that by constructing a grafted layer structure composed of long-chain alkyl and branched alkyl groups on the filler surface, this application can effectively improve the impact breakage resistance of food packaging bags under low-temperature conditions, thereby improving their freezing resistance. The possible reason is that in Comparative Example 1, only long-chain alkyl methacrylate was used to construct the grafted layer. Although this improved the interfacial compatibility between the filler and the polyethylene matrix to some extent, the relatively regular interfacial structure still easily induced the formation of localized high-crystallinity regions around the filler. Under low-temperature conditions, stress concentration easily occurred, leading to easier crack initiation and propagation. In Comparative Example 2, only branched alkyl methacrylate was used to construct the grafted layer. Although this introduced structural disturbance to some extent, the lack of interfacial matching effect from the long-chain alkyl structure resulted in relatively weak bonding between the filler and the polyethylene matrix, which was not conducive to effective stress transfer and dispersion, resulting in poor overall impact resistance of the material.

[0071] As shown in Examples 1-5, the type and proportion of long-chain alkyl methacrylates have a certain influence on the improvement of the freeze resistance of food packaging bags by modified fillers. In Example 1, the mass ratio of lauryl methacrylate to octadecyl methacrylate was 3:1, and a graft layer was formed with 2-ethylhexyl methacrylate. The resulting packaging bag had the lowest drop breakage rate and the highest impact breakage quality after freezing, indicating that the chain length difference of long-chain alkyl groups and the branched structure can form a good synergistic effect at this ratio. Example 2 did not introduce octadecyl methacrylate, so its interface anchoring and chain length difference regulation effects were relatively insufficient. Although octadecyl methacrylate was introduced in Example 3, the proportion of lauryl methacrylate was too high, and the chain length difference regulation effect did not reach the optimal level. In Example 4, the proportion of octadecyl methacrylate was too high, and the tendency of the regular arrangement of long-chain structures in the interface layer was enhanced. In Example 5, only octadecyl methacrylate was used in combination with branched monomers, and the interface layer was relatively easier to form a regular stacking. Therefore, when lauryl methacrylate and octadecyl methacrylate are compounded in an appropriate ratio and further used in conjunction with branched alkyl methacrylate, the modified filler has a more significant effect on improving the low-temperature performance of polyethylene matrix and is more suitable for applications such as frozen food packaging bags.

[0072] Finally, it should be noted that the above embodiments are only used to illustrate the technical solutions of this application, and are not intended to limit them. Although this application has been described in detail with reference to the foregoing embodiments, those skilled in the art should understand that modifications can still be made to the technical solutions described in the foregoing embodiments, or equivalent substitutions can be made to some or all of the technical features therein. Such modifications or substitutions do not cause the essence of the corresponding technical solutions to deviate from the scope of the technical solutions of the embodiments of this application.

Claims

1. A freeze-resistant food packaging bag, characterized in that, It includes the following raw materials by weight: 100 parts low-density polyethylene, 1-5 parts modified filler, and 0.1-1 parts antioxidant; The modified filler has copolymer segments of long-chain alkyl methacrylate and branched alkyl methacrylate grafted onto its surface, wherein the long-chain alkyl ester has 12 to 18 carbon atoms and the branched alkyl ester has 6 to 10 carbon atoms. The modified filler is prepared by the following steps: S1: An aminated filler and a carboxyl-containing trithiocarbonate RAFT chain transfer agent are dispersed in N,N-dimethylformamide, causing an amidation reaction between the aminated filler and the carboxyl-containing trithiocarbonate RAFT chain transfer agent to obtain a RAFT active filler; wherein the aminated filler is obtained by treating silica with an aminosilane coupling agent; the carboxyl-containing trithiocarbonate RAFT chain transfer agent includes 2-methyl-2-[(dodecylthiocarbonyl)thio]propionic acid; S2: 10 parts of RAFT active filler, 4-8 parts of long-chain alkyl methacrylate, 0.5-1.5 parts of branched-chain alkyl methacrylate, and 0.03-0.1 parts of azobisisobutyronitrile are dispersed in 70-120 parts of toluene and reacted at 70-85°C for 5-8 hours under a nitrogen atmosphere to obtain the modified filler; wherein the long-chain alkyl methacrylate includes lauryl methacrylate and octadecyl methacrylate, and the mass ratio of lauryl methacrylate to octadecyl methacrylate is (2-4):

1.

2. The food packaging bag according to claim 1, characterized in that, Step S1 includes: Ten parts of aminated filler, 0.2-1 parts of carboxyl-containing trithiocarbonate RAFT chain transfer agent, 0.1-0.4 parts of N,N'-dicyclohexylcarbonimide and 0.05-0.2 parts of N-hydroxysuccinimide were dispersed in 70-120 parts of N,N-dimethylformamide and reacted at 30-50℃ for 8-12 h under a nitrogen atmosphere to obtain RAFT active filler.

3. The food packaging bag according to claim 1, characterized in that, In step S1, the average particle size of the silica is 0.05~0.2μm.

4. The food packaging bag according to claim 3, characterized in that, The aminated filler was prepared by the following method: Disperse 10 parts of silica and 1-2 parts of aminosilane coupling agent in 100-200 parts of ethanol aqueous solution, and react at 60-80℃ for 3-6 hours to obtain aminated filler.

5. The food packaging bag according to claim 1, characterized in that, The branched alkyl methacrylates include 2-ethylhexyl methacrylate.

6. The food packaging bag according to any one of claims 1 to 5, characterized in that, The raw materials meet at least one of the following conditions: 1) The melt flow rate of the low-density polyethylene at 190℃ and 2.16kg is 1.5~2.5g / 10min; 2) The antioxidants include at least one of antioxidant 1010 and antioxidant 168.

7. A method for preparing freeze-resistant food packaging bags, characterized in that, include: Provide the raw materials included in the food packaging bag according to any one of claims 1 to 6; melt-blend and granulate the raw materials and blown film to obtain the food packaging bag.